ACID ACTIVATION OF PRRENJAS CLAY MINERAL - Mele, A.; Taraj, K.; Korpa, A. (Journal of Engineering & Processing Management, 2015)
Prrenjas clay mineral is found in southeast Albania and has a high content on bentonite. The influence of the sulphuric acid activation on the composition, structure and surface properties of Prrenjas clay mineral is investigated in this study by means of elemental chemical analysis, X-Ray Diffractometry, IR Spectroscopy and gas adsorption-desorption measurement. H 2SO 4 concentrations of 0.143 M, 0.232 M, 0.371 M, 0.537 M, 0.734 M, 0.927 M and 1.456 M were used in the treatment of samples. The treatment by increasing the acid concentration brings the leaching of Al 3+, Fe 2+, Mg 2+ from the clay structure. The specific surface area and the pore volume of the clay samples increases respectively from 83 m 2/g and 0.069 cm 3/g for the untreated clay to 420 m 2/g and 0.384 cm 3 /g for the clay mineral treated with 1.456 M H 2SO 4 solution. New mesopores were created during the acid activation mainly in the range of 2 – 8 nm. For the samples treated with 0.927 M and 1.456 M solutions the increase in specific surface area and pore volume is very high. The cationic exchange capacity decreases steadily with the concentration of H 2SO 4 used for the treatment.